2018
DOI: 10.1016/j.ajog.2017.11.567
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for placental senescence in the genesis of obstetric complications and fetal growth restriction?

Abstract: The placenta ages as pregnancy advances, yet its continued function is required for a successful pregnancy outcome. Placental aging is a physiological phenomenon; however, there are some placentas that show signs of aging earlier than others. Premature placental senescence and aging are implicated in a number of adverse pregnancy outcomes, including fetal growth restriction, preeclampsia, spontaneous preterm birth, and intrauterine fetal death. Here we discuss cellular senescence, a state of terminal prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 134 publications
2
71
0
1
Order By: Relevance
“…Our results suggesting premature placental aging in small fetuses are consistent with those of previous studies showing reduced telomerase activity, shorter telomeres 23,30,32,46 and increased expression of cell senescence markers (p21, p16 and EF-1α) in the placenta of pregnancies with a small fetus 34 . Telomeres are nucleoprotein structures located at the termini of chromosomes that become progressively shorter in each mitotic cycle or due to environmental factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggesting premature placental aging in small fetuses are consistent with those of previous studies showing reduced telomerase activity, shorter telomeres 23,30,32,46 and increased expression of cell senescence markers (p21, p16 and EF-1α) in the placenta of pregnancies with a small fetus 34 . Telomeres are nucleoprotein structures located at the termini of chromosomes that become progressively shorter in each mitotic cycle or due to environmental factors.…”
Section: Discussionsupporting
confidence: 92%
“…Altered placental aging has been described in several obstetric complications 23 including stillbirth 24,25 , spontaneous preterm labor [26][27][28] , poorly controlled maternal diabetes 29 , pre-eclampsia and FGR 30,31 . Previous studies in placentas of pregnancies complicated by FGR showed markers of placental aging, including shorter telomeres, telomerase activity suppression [32][33][34] and increased apoptosis mediated by the p53 pathway [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, acute atherosis has been linked to increased oxidative stress and lipid content in the decidua of preeclamptic women . Oxidative stress is also implicated in the pathophysiology of preeclampsia and fetal growth restriction . Hence, we proposed that macrophages are implicated in the mechanisms leading to oxidative stress, and therefore, obstetrical disease (ie, acute atherosis).…”
Section: Discussionmentioning
confidence: 99%
“…Both DNA damage and oxidative stress are able to induce cellular senescence. Two pathways both initiate and maintain cellular senescence, the p53-p21-pRB and the p16-pRB pathways (Sultana et al, 2018). Induction of either of these converging pathways results in cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%